A phase 1 and randomized controlled phase 2 trial of the safety and efficacy of the combination of gemcitabine and docetaxel with ontuxizumab (MORAb‐004) in metastatic soft‐tissue sarcomas. Issue 14 (29th April 2019) - Jones, Robin L.; Chawla, Sant P.; Attia, Steven; Schöffski, Patrick; Gelderblom, Hans; Chmielowski, Bartosz; Le Cesne, Axel; Van Tine, Brian A.; Trent, Jonathan C.; Patel, Shreyaskumar; Wagner, Andrew J.; Chugh, Rashmi; et al.
Abstract : Background: Ontuxizumab, a humanized monoclonal antibody, targets endosialin (tumor endothelial marker 1 [TEM‐1] or CD248), which is expressed on sarcoma cells and is believed to be involved in tumor angiogenesis. This is the first trial to evaluate ontuxizumab in patients with sarcoma. Methods: Part 1 was an open‐label, dose‐finding, safety lead‐in: 4, 6, or 8 mg/kg with gemcitabine and docetaxel (G/D; 900 mg/m 2 gemcitabine on days 1 and 8 and 75 mg/m 2 docetaxel on day 8). In part 2, patients were randomized in a double‐blind fashion in 2:1 ratio to ontuxizumab (8 mg/kg) or a placebo with G/D. Randomization was stratified by 4 histological cohorts. Results: In part 2 with 209 patients, no significant difference in progression‐free survival between ontuxizumab plus G/D (4.3 months; 95% confidence interval [CI], 2.7‐6.3 months) and the placebo plus G/D (5.6 months; 95% CI, 2.6‐8.3 months) was observed ( P = .67; hazard ratio [HR], 1.07; 95% CI, 0.77‐1.49). Similarly, there was no significant difference in median overall survival between the 2 groups: 18.3 months for the ontuxizumab plus G/D group (95% CI, 16.2‐21.1 months) and 21.1 months for the placebo plus G/D group (95% CI, 14.2 months to not reached; P = .32; HR, 1.23; 95% CI, 0.82‐1.82). No significant differences between the treatment groups occurred for any efficacy parameter by sarcoma cohort. The combination of ontuxizumab plus G/D was generally well tolerated. Conclusions: Ontuxizumab plus G/D showed no enhanced activity over chemotherapy alone in soft‐tissue sarcomas, whereas the safety profile of the combination was consistent with G/D alone. Abstract : Endosialin is involved in tumor blood vessel formation and is expressed on sarcoma tumor cells. This phase 1/2 randomized controlled trial shows that ontuxizumab, an endosialin‐directed monoclonal antibody, does not enhance efficacy in sarcomas when it is combined with chemotherapy (gemcitabine and docetaxel), although the combination is generally well tolerated.